Effect of branching architecture on the self-assembly of symmetric ABC-type block terpolymers. (August 2021) - Li, Luyang; Li, Weihua
Graphical abstract: Abstract: It has been well known that the phase boundaries of AB-type block copolymers can be largely deflected by designing their asymmetric architectures to regulate the stable regions of various ordered phases in a large range. One of the simplest asymmetric architecture is AB n miktoarm star, of which the spherical and cylindrical regions are significantly enlarged by the deflections of the phase boundaries toward large volume fraction of A-block. Accordingly, we design a symmetric ABC-type pentablock terpolymer by branching B-blocks, i.e. connecting one of the B-arms of a pair of miktoarm star copolymers AB 2 and CB 2 together. This symmetric pentablock terpolymer is composed of two equal A and C blocks tethered on a B-chain. We investigate the self-assembly behaviors of this terpolymer using self-consistent field theory, focusing on the control of the length ratio of the middle B-block to the total B-blocks on the regions of alternating spherical, cylindrical and gyroid phases. It is predicted that the three phase regions are successfully regulated in a large range by the architectural parameter, which are accompanied by a lot of interesting phase behaviors. For instance, an unusual order-order transition from the spherical phase to the gyroid phase with the absence of the cylindrical phase is determined. Our results reveal that these interesting phase behaviors result from three sophisticated effects including the branching effect on the spontaneous curvature, the released packing frustration from different B-blocks and the stretched bridging middle B-block.